Steroid effects on secretion from subsets of lactotrophs: role of folliculo-stellate cells and annexin 1. - Morris, J; Christian, H; Chapman, L; Epton, M; Buckingham, J; Ozawa, H; Nishi, M; Kawata, M (2002)
Prolactin secretion is controlled by the hypothalamus, and by circulating steroids; oestrogens stimulate, but glucocorticoids inhibit prolactin release. Lactotrophs express intracellular receptors for oestrogens, but apparently not glucocorticoids. Therefore, a genomic effect of oestrogens could be direct, but that of glucocorticoids appears to be indirect. Lactotrophs are not a homogeneous cell population: some have large irregular dense-cored vesicles, others have small round vesicles, but the functional significance of this inhomogeneity is far from clear. Oestradiol and testosterone can stimulate rapid release of prolactin selectively from type II lactotrophs characterised by small round vesicles. Progesterone and other steroids do not exert this effect, which results from a non-genomic action of oestradiol and testosterone. Glucocorticoid inhibition of secretagogue-induced prolactin secretion is mimicked by annexin 1 (lipocortin 1), a protein induced by glucocorticoids in the pituitary and many other tissues, and can be blocked by annexin 1 immunoneutralisation and antisense. Glucocorticoid inhibition of ACTH and growth hormone secretion also involves annexin 1. Pituitary annexin 1 is located in folliculo-stellate cells; these express glucocorticoid receptors, and glucocorticoids induce annexin-1 synthesis. Annexin 1 is externalised from folliculo-stellate cells in response to glucocorticoids, despite the fact that it lacks a secretory signal sequence and is not packaged in vesicles. Inhibition of annexin 1 externalisation by glyburide suggests involvement of an ABC (ATP-binding cassette) transporter in externalisation. Both oestradiol and glucocorticoids therefore influence the secretion of prolactin by novel direct and indirect mechanisms, in addition to their much better understood effects on transcription via classical intracellular steroid receptors.